OP52 To what extent do online resources meet the needs of substitute decision-makers in australia? Part 2. Issue Volume 9: Issue (2019)Supplement 2 (3rd December 2019) - Sellars, M; Tran, J; Nolte, L; White, B; Sinclair, C; Fetherstonhaugh, D; Detering, K
Abstract : Background: We aimed to examine Australians' knowledge, attitudes and experiences regarding the role of substitute decision-makers (SDMs). SDMs may also be known as 'surrogate' or 'proxy' decision-makers. Methods: A national survey was distributed via an online panel in September 2018 to 1, 484 adults aged 18 years and over. Quotas on age, gender and jurisdiction (based on 2017 Australian Census data) aimed to maximise representativeness. Results: Of the 1, 058 survey completers (response rate=71.3%), the majority (67%) did not know there were laws about substitute decision-making and 12% had previously made medical decisions on behalf of someone else. Seventy-four percent of those with SDM experience (n=97) agreed that making medical decisions on someone's behalf can be a difficult and stressful experience compared to 56% of those without SDM experience (n=589). Moreover, only 38% of those without SDM experience indicated they would feel confident in the role of SDM. When asked their preferred source for receiving SDM information, 59% of all respondents ranked health professional as their first preference, followed by discussion with family or friends (23%), traditional media (7%), new media (6%) or an event (3%). Only 16% indicated that appointing a SDM was a priority at the time of completing the survey. Conclusion(s): Among a representative sample of Australians it was relatively common to have acted in the role of SDM and most who had perceived the role as challenging. Further education and support is needed to clarify roles, relevance and benefits in appointing and preparing SDMs.